Dogmatiek in die rigting van die Gereformeerde Ortodoksie? - Koekemoer, J. H. (Verbum et ecclesia, 1994)
Dogmatics in the direction of Reformed orthodoxy J. A. Heyns plays a significant role in doing theology in the South African context. A critical analysis of his work in the field of dogmatics indicates a movement in the direction of Reformed orthodoxy. This article is a first step towards a theological discussion with him on this issue.